2022
DOI: 10.1007/s10570-022-04889-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose acetate/polyvinylidene fluoride based mixed matrix membranes impregnated with UiO-66 nano-MOF for reverse osmosis desalination

Abstract: Reverse osmosis (RO) is considered a lifesaver technology to conquer the current catastrophic water shortage situation. However, reaching a competitive RO membrane is a challenging issue. Therefore, this study investigated the optimum polymeric blending ratio between cellulose acetate (CA) and polyvinylidene fluoride (PVDF) to have a new blended polymeric membrane named cellulose acetate polyvinyl (CAPV-X), where X is the PVDF concentration %, with enhanced properties. The optimum prepared CA/PVDF blended memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Such hysteresis loops are observed in natural materials and signify aggregation of slit-shaped pores organized hierarchically. It has already been evidenced that delignification creates microporosity in the lignin matrix [24,25] . The specific BET measurements reveal the surface area as 44.65 and 54.83 m 2 g -1 for NW and TrW, while the average pore diameters are 7.97 and 6.08 nm for NW and TrW, respectively [Supplementary Table 1].…”
Section: Wood Modification and Characterizationmentioning
confidence: 99%
“…Such hysteresis loops are observed in natural materials and signify aggregation of slit-shaped pores organized hierarchically. It has already been evidenced that delignification creates microporosity in the lignin matrix [24,25] . The specific BET measurements reveal the surface area as 44.65 and 54.83 m 2 g -1 for NW and TrW, while the average pore diameters are 7.97 and 6.08 nm for NW and TrW, respectively [Supplementary Table 1].…”
Section: Wood Modification and Characterizationmentioning
confidence: 99%
“…Then, the resulting membrane is heated for annealing. Finally, the resulting RO membrane is stored in water for further uses [26,[44][45][46][47][48]98].…”
Section: Cellulose Acetate Ro Membranementioning
confidence: 99%
“…The CA-RO membranes have been used for desalination [46,48,99,100], to remove ammonium from aqueous solutions [101], a trace of organic compounds and micropollutants are rejected from water more effectively by the CA-RO membranes [102], and fermentation broth separation [103].…”
Section: Cellulose Acetate Ro Membranementioning
confidence: 99%
“…In recent research, PVDF membranes have been modified by incorporating natural polymers such as cellulose. Several studies have reported excellent performance of PVDF membranes reinforced with cellulose, including high flux, strong rejection, high porosity, and excellent anti‐fouling properties [20,23–26] . This is primarily attributed to the hydroxyl groups of these natural polymers, which have been shown to enhance the formation of the beta phase in PVDF [27] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported excellent performance of PVDF membranes reinforced with cellulose, including high flux, strong rejection, high porosity, and excellent anti-fouling properties. [20,[23][24][25][26] This is primarily attributed to the hydroxyl groups of these natural polymers, which have been shown to enhance the formation of the beta phase in PVDF. [27] As a result, the hydrophilicity of PVDF membranes also increases, significantly reducing fouling effects.…”
Section: Introductionmentioning
confidence: 99%